1991
DOI: 10.1111/j.2042-7158.1991.tb03537.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Imipramine on the Membrane Anisotropy and on the Phospholipid Methylation in the Central Nervous System of the Rat

Abstract: An ex-vivo and in-vitro study of the effects of imipramine on the membrane anisotropy and phospholipid methylation in the rat cortical membranes was carried out. A comparative study of the membrane fluidity in various brain regions indicated different basal anisotropy of the areas and different reaction of these membranes to imipramine. It was found that imipramine when given to rats chronically (14 x 10 mg kg-1, i.p.) or added externally to the cortical membranes of naive rats or rats treated with a single do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The lack of significant alterations in the level of cyclic AMP in the slices of CP obtained from control animals induced by 10 μM GppNHp may result from mixed effect on different populations of G proteins. On the other hand, following administration of imipramine, such changes take place either in the fluidity of the cell membrane — as described previously by Melzacka and Nocon (1991) — or at the very level of G i proteins themselves, that inhibition of adenylate cyclase becomes apparent. Indeed, ex vivo (i.e.…”
Section: Discussionmentioning
confidence: 77%
“…The lack of significant alterations in the level of cyclic AMP in the slices of CP obtained from control animals induced by 10 μM GppNHp may result from mixed effect on different populations of G proteins. On the other hand, following administration of imipramine, such changes take place either in the fluidity of the cell membrane — as described previously by Melzacka and Nocon (1991) — or at the very level of G i proteins themselves, that inhibition of adenylate cyclase becomes apparent. Indeed, ex vivo (i.e.…”
Section: Discussionmentioning
confidence: 77%
“…Tricyclic antidepressants decreased the anisotropy values of HEK-5-HT 3A cells in the upper micromolar range, indicating an increase in membrane fluidity, as it has been observed in different membrane preparations from rat brains. 38,39 In addition, spin-label studies suggested an increase in membrane fluidity after a treatment with DMI and imipramine at low micromolar concentrations. 40 However, in rat synap- Values (mean7SEM; n=3-4) indicate percent of the control current; ND=not determined.…”
Section: Discussionmentioning
confidence: 99%